Optimisation of Solid-Phase Extraction and LC-MS/MS Analysis of Six Breast Cancer Drugs in Patient Plasma Samples - Lu Turković; Dragana Mutavdžić Pavlović; Zvonimir Mlinarić; Anamarija Skenderović; Tajana Silovski; Miranda Sertić (MDPI AG, 2023)
In the development of bioanalytical LC-MS methods for the determination of drugs in plasma samples in a clinical setting, adequate sample preparation is of utmost importance. The main goals are to achieve the selective extraction of the analytes of interest and attain thorough matrix removal while retaining acceptable ecological properties, cost-effectiveness, and high throughput. Solid-phase extraction (SPE) offers a versatile range of options, from the selection of an appropriate sorbent to the optimisation of the washing and elution conditions. In this work, the first SPE method for the simultaneous extraction of six anticancer drugs used in novel therapeutic combinations for advanced breast cancer treatment-palbociclib, ribociclib, abemaciclib, anastrozole, letrozole, and fulvestrant-was developed. The following sorbent chemistries were tested: octylsilyl (C8), octadecylsilyl (C18), hydrophilic-lipophilic balance (HLB), mixed-mode cation-exchange (MCX and X-C), and mixed-mode weak cation-exchange (WCX), with different corresponding elution solvents. The samples were analysed using LC-MS/MS, with a phenyl column (150 × 4.6 mm, 2.5 μm). The best extraction recoveries (≥92.3%) of all analytes were obtained with the C8 phase, using methanol as the elution solvent. The optimised method was validated in the clinically relevant ranges, showing adequate precision (inter-day RSD ≤ 14.3%) and accuracy (inter-day bias −12.7-13.5%). Finally, its applicability was successfully proven by the analysis of samples from breast cancer patients.